Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's break down the problem step-by-step to identify which expression represents the converse of a given conditional statement [tex]\( p \rightarrow q \)[/tex].
1. Understanding the Conditional Statement [tex]\( p \rightarrow q \)[/tex]:
- [tex]\( p \rightarrow q \)[/tex] means "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".
- In this context, [tex]\( p \)[/tex] is the hypothesis (or antecedent) and [tex]\( q \)[/tex] is the conclusion (or consequent).
2. Defining the Converse:
- The converse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is obtained by swapping the hypothesis and the conclusion. Therefore, the converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex].
3. Evaluating the Options:
- [tex]\(\sim p \rightarrow -q\)[/tex]: This expression states "if not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]". This does not swap the hypothesis and conclusion; it involves negations.
- [tex]\(\sim q \rightarrow \sim p\)[/tex]: This expression states "if not [tex]\( q \)[/tex], then not [tex]\( p \)[/tex]". This still does not represent the converse of the original statement.
- [tex]\(q \rightarrow p\)[/tex]: This expression correctly states "if [tex]\( q \)[/tex], then [tex]\( p \)[/tex]", which is precisely the converse of [tex]\( p \rightarrow q \)[/tex].
- [tex]\(p \rightarrow q\)[/tex]: This is the original conditional statement, not its converse.
From this detailed analysis, we can conclude that the correct answer, which represents the converse of the conditional statement [tex]\( p \rightarrow q \)[/tex], is:
[tex]\[ q \rightarrow p \][/tex]
1. Understanding the Conditional Statement [tex]\( p \rightarrow q \)[/tex]:
- [tex]\( p \rightarrow q \)[/tex] means "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".
- In this context, [tex]\( p \)[/tex] is the hypothesis (or antecedent) and [tex]\( q \)[/tex] is the conclusion (or consequent).
2. Defining the Converse:
- The converse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is obtained by swapping the hypothesis and the conclusion. Therefore, the converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex].
3. Evaluating the Options:
- [tex]\(\sim p \rightarrow -q\)[/tex]: This expression states "if not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]". This does not swap the hypothesis and conclusion; it involves negations.
- [tex]\(\sim q \rightarrow \sim p\)[/tex]: This expression states "if not [tex]\( q \)[/tex], then not [tex]\( p \)[/tex]". This still does not represent the converse of the original statement.
- [tex]\(q \rightarrow p\)[/tex]: This expression correctly states "if [tex]\( q \)[/tex], then [tex]\( p \)[/tex]", which is precisely the converse of [tex]\( p \rightarrow q \)[/tex].
- [tex]\(p \rightarrow q\)[/tex]: This is the original conditional statement, not its converse.
From this detailed analysis, we can conclude that the correct answer, which represents the converse of the conditional statement [tex]\( p \rightarrow q \)[/tex], is:
[tex]\[ q \rightarrow p \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.